Renewable Portfolio Standards for the Promotion of Renewable Energy - The Dilemma of Developmental Inequity in the United States - Seyboth,Kristin (2006)
Implementation of the Renewable Portfolio Standard (RPS), a political tool intended to increase investment in renewable energy, has become increasingly common in the early 21st century. RPS policies require that a certain amount, or percentage, of electricity in a providers electricity supply mix is generated from renewable energy sources. The distribution of renewable energy generation capacity development which has resulted from the implementation of RPS policies in the United States was investigated in this thesis research. As it relates, the political implications of developmental inequity which may result from RPS policies was also investigated. This thesis research presents a link between the geographic distribution of the installed renewable energy generation capacity that has resulted from the implementation of state RPS policies and corresponding boundary definitions of Tradable Renewable Energy Credit (TREC) markets. TRECs, which represent the renewable attributes of electricity generated from renewable energy generation installations, are often included in RPS policies as a compliance and flexibility mechanism. Several American states have declared TRECs generated by out-of-state renewable energy generation facilities eligible for RPS compliance in their state, thereby extending their TREC compliance market boundaries. As a result, it was found that much of the renewable energy credited for RPS compliance in those states with extended TREC market boundaries, is generated outside of that state which implemented the policy. As such, those states which have included an extended TREC compliance market in accordance with their RPS have developed comparatively less in-state renewable energy capacity than states which have restricted compliance eligibility to renewable energy facilities to a more regional, or state-wide market. The development of new installed renewable energy generation capacity that results from RPS policies may therefore be displaced to neighbouring regions if an extended TREC compliance market is included in the policy design. Additionally, this thesis research was supplemented with a presentation of the effects of RPS on renewable energy generation installations by technology type. Following the implementation of RPS, wind energy generation, a comparably low cost renewable energy technology, was found to have been disproportionately successful in comparison with alternative renewable energy technologies. Based upon the geographic and industrial distribution patterns of renewable energy generation capacity installations that have resulted from state RPS policies, the likely distribution of development that would result from a federal RPS is presented and discussed. If a federal RPS were to include a national-scale TREC compliance market, large increases in wind energy installations, especially within the Upper Midwestern states, have been projected. Trends in American politics, which were found to favour equity and regional economic development in policy design, seem to stand in opposition to this possible developmental inequity. As such, it is recommended that a federal RPS, if implemented, should take into consideration design features which act to limit inequity. Such design features could include a TREC compliance market with regional boundaries, specifications for TREC allowances in regions with less indigenous resource, or an altogether exclusion of a national-scale TREC compliance market. As such, national goals to foster the implementation of an increased percentage of renewable energy generation capacity may simultaneously achieve political goals for geographic equity through the implementation of RPS.
Keywords: Renewable Portfolio Standard; Tradable Renewable Energy Credit; Distributional Equity; Developmental Inequity; United States; Environmental studies; Miljöstudier